2015
DOI: 10.21149/spm.v57i1.7402
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of aflatoxin B1 during tortilla production and identification of degradation by-products by direct-injection electrospray mass spectrometry

Abstract: Objective. To determine the effect of pH, and exposure time over the inactivation of aflatoxin B 1 (AFB 1 ) during the tortilla making process as well as the degradative molecules generated. Materials and methods. Inactivation of AFB 1 in maize-dough with alkaline pH and in alkaline methanolic solutions was determined by HPLC. Kinetics of time exposure of AFB 1 in methanolic solution and the degradative products were analyzed by direct injection electrospray mass spectometry (DIESI-MS). Results. The alkaline p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 23 publications
(20 reference statements)
3
13
0
Order By: Relevance
“…It was evident that the pH along with the process parameters synergistically affected the aflatoxin content in the matrix. The result obtained were in accordance with the result reported by Rustom et al (1993), M endez-Albores et al (2013) and Moreno-Pedraza et al (2015).…”
Section: Influence Of Ph On Aflatoxin Reductionsupporting
confidence: 93%
See 3 more Smart Citations
“…It was evident that the pH along with the process parameters synergistically affected the aflatoxin content in the matrix. The result obtained were in accordance with the result reported by Rustom et al (1993), M endez-Albores et al (2013) and Moreno-Pedraza et al (2015).…”
Section: Influence Of Ph On Aflatoxin Reductionsupporting
confidence: 93%
“…The results obtained for the effect of pH were in accordance with the results published by Méndez‐Albores et al () in which it was stated that as the alkali concentration increased, lower aflatoxin values were registered. Moreno‐Pedraza et al () also have reported that pH values around neutral (pH 8.0 only 19.10%) were much less effective in destroying aflatoxins than more alkaline conditions (at pH 11.8 and 12.5, it was by reduced 90 and 100% respectively).The analysis for the respective optimized parameters proved to be at a closer range to the predicted values. The combination treatment, where the spiked PDA was PEF treated and then subjected to thermal treatment was found to be higher than the individual process effect.…”
Section: Resultsmentioning
confidence: 60%
See 2 more Smart Citations
“…Studies show that Alumino-silicates have wide variation of these elements ( Table 1). In South American countries, ashes such as soda ash and wood ash have been used in some food processes such as in niztamalization for corn tenderization where dietary aflatoxins load is also reduced owing to breakage of aflatoxin lactone-ring by the ash alkalinity (19). In Tanzania farmers are using an imported binder that has proven to be useful in terms of protecting livestock from aflatoxin exposure.…”
Section: Introductionmentioning
confidence: 99%